E-Learning-Webseite als facettenreiches Werkzeug in Forschung und Lehre - Günter Daniel Rey; Fabian Beck (FernUniversität Hagen, 2010)
In the context of blended learning a web page might provide accompanying material for a course or encourage students to participate actively in preparing content. Moreover, such a web page could be a platform for e-learning research and empirical studies might be embedded into the page. The analysis of the user's behavior can be applied to verify current research results concerning learning with hypermedia. We describe such a versatile web page, which combines university apprenticeship and research. First experiences are reported and may lead to similar projects as well as convey selected recommendations for lecturer and researcher.